35. BUILDING AN INTERVENTION MODEL FOR THE PREVENTION AND SCREENING OF CERVICAL CANCER IN WOMEN OF REPRODUCTIVE AGE IN DIEN BIEN PROVINCE (Vietnam Journal of Community Medicine, 2024)
Objective: Research and develop a model of cervical cancer prevention and screening intervention for women of reproductive age from 15-49 years old in Dien Bien province.Research methods: Cross-sectional descriptive study, controlled intervention.Results: The proportion of subjects with correct knowledge about cervical cancer prevention was 16.3%; HPV prophylactic vaccination rate is 3.3%; the rate of women having regular prenatal check-ups reached 49.2%; after intervention, the change in knowledge increased by 18.7%; vaccination practice efficiency increased by 6.9%; the effectiveness of changing access to periodic examination services increased by 12.3%. To prevent cervical cancer, it is necessary to synchronously deploy solutions: strengthening communication work, vaccination to prevent cervical cancer and expanding screening services at the commune level to make it convenient for people. convenient access to services.Conclusion: It is necessary to strengthen measures in both medical expertise and communication to enhance cervical cancer prevention for women in Dien Bien province in particular and women in general.
Keywords: Cervical cancer; HPV prophylactic vaccination; Health sector of Dien Bien province